(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article presents the views on the issues of financial risk and financial security encountered in industrial enterprises of our country. In addition, considerations and conclusions are made regarding the type of financial risks related to technological aspects.